The Universe Is on Our Side Restoring Faith in American Public Life - Ledewitz, Bruce 1975- (Oxford Oxford University Press USA - OSO, 2021)
In The Universe Is On Our Side, Bruce Ledewitz argues that there has been a breakdown in American public life that no election can fix -Americans struggle to even converse about politics and the usual explanations for our condition have failed to make things better. America's future requires that we begin a new story by each of us asking a question posed by theologian Bernard Lonergan: Is the universe on our side? According to Ledewitz, when we commit to live honestly and fully by our answer to that question, even if our immediate answer is no, America can begin to heal.
Cover -- Half Title page -- The Universe Is on Our Side -- Copyright -- Dedication -- Epigraph -- Contents -- Acknowledgments -- Prologue -- Introduction -- PART I. THE DEATH OF GOD COMES HOME TO ROOST -- 1. The Breakdown in American Public Life -- 2. The Spiritual Dimension of the Breakdown -- 3. The Arrival of the Death of God -- 4. Faithless American Public Life -- 5. The Age of Evasion -- PART II. RESTORING FAITH IN AMERICAN PUBLIC LIFE -- 6. Is the Universe on Our Side? -- 7. No, the Universe Is Not on Our Side -- 8. Yes, the Universe Is on Our Side -- 9. Restored Public Life -- 10. Does This Bring Us Back to God? -- Afterword -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Religion and politics-United States-History; United States-Politics and government-21st century-Public opinion; Electronic books